(untitled) (Baghdad Science Journal, 2006)
Studied the environment and fish life Qattan in the Euphrates River in central Iraq for the period from September 2002 until 2003 recorded the lowest temperature of the water during the month of January during the month of August ranged salinity ranges between 068